Magika Empire Sdn Bhd / Nur Batrisyia Mohamed Nizam Shah - Mohamed Nizam Shah, Nur Batrisyia (Faculty of Business and Management, 2023)
I am excited to share my experiences with Magika Empire Sdn. Bhd. with you, and I hope that you will find them as enlightening as I did. The following report provides a comprehensive overview of the internship project conducted over a duration of six months at Magika Empire Sdn Bhd. The internship occurred on March 1st and concluded on August 15th, 2023. This detailed report comprises various aspects, including an overview of the student's resume, a comprehensive background of Magika Empire Sdn Bhd, its history, vision, mission, objectives, and goals. Furthermore, the report digs into the organizational structure of the company, enlightens on its hierarchical framework, key departments, and the range of products and services offered by the organization. A crucial component of the report are the SWOT analysis specifically focused on the Magika HQ. The primary objective of this report is to showcase the execution of a SWOT analysis throughout the six-month industrial training period. It highlights the tasks undertaken, skills acquired, knowledge gained, and achievements accomplished by the student. It is important to note that the internship mainly took place within the marketing sector of Magika HQ, thus the students were exposed to the work procedures, the work environment and organizational culture. Additionally, the report encompasses valuable recommendations and proposed solutions to address identified issues. The student demonstrated a keen ability to tackle these challenges by employing effective problem-solving techniques. The practical knowledge acquired during the internship period facilitated the application of communication, problem-solving, and management skills in real-world scenarios. Upon the successful completion of the internship, the student obtained a great understanding of organizational operations and gained invaluable hands-on experience in the workplace. This experience not only enhanced their professional skills but also provided invaluable insights into workplace dynamics and behavioral expectations.